2020
DOI: 10.1371/journal.pone.0241040
|View full text |Cite
|
Sign up to set email alerts
|

Altered shear stress on endothelial cells leads to remodeling of extracellular matrix and induction of angiogenesis

Abstract: Endothelial cells (ECs) are subjected to physical forces such as shear stress (SS) induced by blood flow that leads to significant changes in morphology, physiology and gene expression. The abnormal mechanical forces applied in the cardiovascular system can influence the development of conditions and diseases such as thrombosis, hypertension and atherosclerosis. This study investigated the expression of glycosaminoglycans (GAGs), proteoglycans and extracellular matrix molecules in ECs exposed to normal and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 55 publications
(62 reference statements)
3
32
0
Order By: Relevance
“…Similar to our experimental model, Russo and colleagues [72] demonstrated that rabbit aortic endothelial cells exposed for 4 h to sub-physiological and physiological values of shear stress have a different tendency to form tube-like structures. Moreover, they confirmed that mRNA expression of pro-angiogenic factors such as vascular endothelial growth factor A (VEGF-A), transforming growth factor-beta 1 (TGF-β1) and transforming growth factor-beta 3 (TGF-β3) is higher in EC cells exposed to pathological shear stresses compared to physiological shear stress.…”
Section: Discussionsupporting
confidence: 78%
“…Similar to our experimental model, Russo and colleagues [72] demonstrated that rabbit aortic endothelial cells exposed for 4 h to sub-physiological and physiological values of shear stress have a different tendency to form tube-like structures. Moreover, they confirmed that mRNA expression of pro-angiogenic factors such as vascular endothelial growth factor A (VEGF-A), transforming growth factor-beta 1 (TGF-β1) and transforming growth factor-beta 3 (TGF-β3) is higher in EC cells exposed to pathological shear stresses compared to physiological shear stress.…”
Section: Discussionsupporting
confidence: 78%
“…Collagen I is well established as a 2D coating or 3D ECM for endothelial cells, as it robustly supports adherence and monolayer formation 49 , 55 58 . In contrast, studies on culturing endothelial cells on basement membrane extracts (BMEs) such as geltrex or matrigel focus on induction of tube formation, modelling angiogenesis 62 64 . Our initial findings mirror these approaches, with successful vessel formation on collagen I, and vessel retraction and tube formation against geltrex.…”
Section: Discussionmentioning
confidence: 99%
“…HS accounts for 50–90% of the total GAG pool, while the rest is composed of CS and hyaluronan [ 10 ]. In a recent study, endothelial cells exposed to pathological shear stress increased GAG synthesis, secretion and content, compared with those exposed to physiological shear stress [ 11 ▪ ]. The extent of atherosclerosis progression is associated with thinning of vascular endothelial glycocalyx, attributed to diminished expression of HSPGs [ 12 ▪ ].…”
Section: Proteoglycans and Their Glycosaminoglycans In Atherosclerosismentioning
confidence: 99%